2015
DOI: 10.37052/ml.28(1)no6
|View full text |Cite
|
Sign up to set email alerts
|

The Translation of Foreign Novels into Malay by Dewan Bahasa dan Pustaka

Abstract: Established in 1956 with the main purpose of developing the Malay language, Dewan Bahasa dan Pustaka (DBP) has also played a pivotal role in the translation of foreign works into Malay. Very little, however, has been studied in terms of its contribution to the development of translation activities in Malaysia. This paper aims to provide an overview of the translation of foreign novels into Malay by DBP from the time of its inception. A survey was carried out for this purpose. The results show that a total of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Hanya sebilangan kecil para sarjana berkecimpung aktif dalam penterjemahan karya sastera Arab di Malaysia, iaitu Shamsuddin Jaffar, A. K. Zain, Osman Haji Khalid, Muhammad Bukhari Lubis, Nahmar Jamil dan Sohair Abdul Moneim Sery (Ahmad, 2011). Manakala sehingga tahun 2001, Dewan Bahasa dan Pustaka didapati hanya menerbitkan empat buah sahaja novel terjemahan bahasa Arab ke bahasa Melayu (Haroon & Abdul Majid, 2015). Antaranya ialah novel bertajuk Lorong Midaq (1984) karya Naguib Mahfouz, iaitu Zuqaq al-Midaq, Hanya Semalam (1987 karya Kulit Suhail bertajuk Laila Wahidah dan Duri-duri Liar (1992) karya Sahar Khalifeh bertajuk Wild Thorns (Raja Ariffin, 2008).…”
Section: Sejarah Awal Terjemahan Karya Sastera Prosa Arab Ke Bahasa M...unclassified
“…Hanya sebilangan kecil para sarjana berkecimpung aktif dalam penterjemahan karya sastera Arab di Malaysia, iaitu Shamsuddin Jaffar, A. K. Zain, Osman Haji Khalid, Muhammad Bukhari Lubis, Nahmar Jamil dan Sohair Abdul Moneim Sery (Ahmad, 2011). Manakala sehingga tahun 2001, Dewan Bahasa dan Pustaka didapati hanya menerbitkan empat buah sahaja novel terjemahan bahasa Arab ke bahasa Melayu (Haroon & Abdul Majid, 2015). Antaranya ialah novel bertajuk Lorong Midaq (1984) karya Naguib Mahfouz, iaitu Zuqaq al-Midaq, Hanya Semalam (1987 karya Kulit Suhail bertajuk Laila Wahidah dan Duri-duri Liar (1992) karya Sahar Khalifeh bertajuk Wild Thorns (Raja Ariffin, 2008).…”
Section: Sejarah Awal Terjemahan Karya Sastera Prosa Arab Ke Bahasa M...unclassified
“…Sanchez Ortiz (2015), meanwhile, examined four Spanish translations of Oscar Wilde's novel The Picture of Dorian Gray and found that the four translators differed in their use of footnotes. In the Malaysian context, the study carried out by Haroon and Abdul Majid (2015) found that some of the book translations into Malay published by the national language and literary agency of Malaysia, Dewan Bahasa dan Pustaka, do contain footnotes, which perform an explanatory function in the texts (p. 143). The study, however, does not provide any quantitative analysis on the use of footnotes in translation as it does not focus specifically on this aspect.…”
Section: Introductionmentioning
confidence: 99%